Interaction of seawater microorganisms with scalants and antiscalants in reverse osmosis systems - Mohammad Yousaf Ashfaq (17017761) (2020)
In this research, the interactions of seawater microorganisms with scalants (minerals like calcium sulfate) and antiscalants in the reverse osmosis (RO) systems were investigated. The interaction of seawater microorganisms with antiscalants was investigated by measuring the growth of bacteria in an antiscalant containing growth medium, which was added as a sole source of carbon and energy. Moreover, the interaction of microorganism with calcium sulfate (selected as a model scalant) was also investigated using scanning electron microscopy – energy dispersive x-ray spectroscopic technique. It was found that several Pseudomonas strains isolated from the marine water of Qatar are capable of using antiscalants as an energy or carbon source. It was noted that the growth curves of the strains vary with the type of the antiscalant studied. Furthermore, the results of microorganism-scalant interaction showed that the presence of bacteria induced/mediated precipitation of calcium sulfate on the RO membranes, whereas, no precipitation was noted on the control RO membranes (i.e. without bacteria) under the studied conditions. Therefore, the results of this research showed that the presence of microorganisms in seawater reverse osmosis not only causes biofouling but also enhances mineral scaling through biodegradation of antiscalants and precipitation of minerals (calcium sulfate). Other Information Published in: Desalination License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.desal.2020.114480